IMPLEMENTASI KURIKULUM 2013 PADA BIDANG STUDI PENDIDIKAN AGAMA ISLAM KELAS XI SMK NEGERI 3 PAREPARE - Haizah Haizah (IAIN PAREPARE, 2017)
This paper aimed to empirically determine and describe: lesson planning in the 2013 curriculum, the implementation of the 2013 curriculum, learning assessment conducted by the class XI teacher of Pendidikan Agama Islam at SMK Negeri 3 Parepare. The method aiming at describing an existing phenomenon and its true condition by using observation techniques, interview, and studying documents. The data were then analyzed by following the steps of (1) data reduction; (2) data presentation; (3) the data conclusion and verification. The results of the study showed that to date SMK Negeri 3 is still applying 2013 curriculum as its reference for a learning process. The implementation of the 2013 curriculum was determined by (1) lesson planning; (2) learning implementation; and (3) learning assessment. At the stage of lesson planning, teacher designs lesson plan which are then implemented in learning process by applying a scientific approach consisting of the following stages: (1) observing; (2) questioning; (3) collecting materials; (4) processing materials; and (5) communicating, which is then followed by administering authentic assessment on the learning in the forms of: (1) observation; (2) oral and written test; (3) self assessment; (4) peer-assessment; (5) journal; (6) performance assessment; and (7) portfolio assessment. Factors that support the implementation of the 2013 curriculum include (1) teacher; (2) learners; (3) infrastructure and facilities; and (4) environment. On the other hand, the hindering factors are (1) lack of learners’ care with their lessons; (2) lack of teachers’ understanding of 2013 curriculum due to minimum education and training.